2011
DOI: 10.5455/jeim.080411.or.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical melatonin and vitamin E in a rat ischemic wound model

Abstract: Objective: Reactive oxygen species are known to increase on a chronic wound background. We therefore investigated the possible efficacy of the topical administration of melatonin and vitamin E, known to have radical scavenging properties, in the ischemic wound model.Methods: Forty Sprague-Dawley type adult male rats were divided into 4 groups as normal wound, ischemic group, and with vitamin E or melatonin applied to the ischemic wound. Bipedicular flap surgery to the shaved back of the rats was used to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Additionally, it is a potent ROS-scavenger [17][18][19]. MEL and its metabolites have also powerful anti-inflammatory properties and have proven to be highly effective in a variety of disorders linked to oxidative stress and inflammation in experimental animals [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is a potent ROS-scavenger [17][18][19]. MEL and its metabolites have also powerful anti-inflammatory properties and have proven to be highly effective in a variety of disorders linked to oxidative stress and inflammation in experimental animals [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it showed antioxidant efficacy through decreasing MDA levels (Ozler et al, 2011). Although melatonin was administered at an amount of 3 mg per wound in the present study, in the study conducted by Ozler et al (2011), melatonin was administered at an amount of 0.1 mg per wound. Similar to our results, topical administration of melatonin (5 mg melatonin per rat and twice a day) decreased both MDA and MPO level in injured skin in rats with pressure ulcers (Sener et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ozler et al (2011) showed that topically applied melatonin (5 mg/kg) in ischemic wounds had neither a positive nor a negative effect on hydroxyproline levels. However, it showed antioxidant efficacy through decreasing MDA levels (Ozler et al, 2011). Although melatonin was administered at an amount of 3 mg per wound in the present study, in the study conducted by Ozler et al (2011), melatonin was administered at an amount of 0.1 mg per wound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations